Claves epistemológicas para la formación de investigadores educativos - Bermudez Garcia, José Ángel (2018)
The formation for scientific praxis of the educational researchers of our University is developed under the positivist mentality, promoting an educational culture of the ironical instrumental and recipes logic. It is exposed the serious epistemological crisis, an ontological and anthropological vacuum when it comes to understanding reality. This research approaches existentially to the epistemological keys that can contribute to think the formative processes and the scientific praxis of the educational researchers to inscribe them in the way of the new consciential science that is being born contemporaneously. The methodological path through which theresearch takes place is the Systematization of Experiences. From the systematized experiences emerged three key theoretical keys for reflection in the context of university education, which are: (a) renewed scientific thinking; (b) education and research with existential character and; (c) from methodolatri to scientific methodology.